Enhanced friction and wear behavior of submicron WC-reinforced Cu matrix composites at various temperatures - Zhimin Zhang; Shixin Xu; Kailing Xiang; Ning Guo; Liming Zhong; Ke Feng; Ke Zhu; Yake Wu; Feng Jiang (Journal of Materials Research and Technology)
In this study, submicron tungsten carbide (WC)-reinforced Cu matrix composites (WC/Cu) were fabricated using an extensible manufacturing process (flake powder metallurgy of WC/Cu master alloy, casting and cold rolling of WC/Cu ingots). X-ray diffraction (XRD), energy dispersive spectroscopy (EDS) and electron backscatter diffraction (EBSD) techniques were jointly employed to characterize phases and microstructures of the as-cast and rolled WC/Cu composites. The friction and wear behavior of these composites was investigated at different temperatures (25, 100, and 300 °C). The results indicate that a significant amount of submicron WC particles was successfully incorporated into the Cu matrix. As cold rolling deformation increases, the pseudo-dispersion of WC particles diminishes, resulting in a more uniform particle distribution. A comparison of wear volume losses under various conditions shows a significant improvement in the wear resistance of the WC/Cu composite compared to pure Cu. Notably, the NC1 (with a 20% rolling reduction) and NC2 (with an 80% rolling reduction) samples exhibit outstanding wear resistance at 300 °C, with lower wear volume loss than at 25 and 100 °C. Such improvement is attributed to the reinforcement of the oxide film at 300 °C by the addition of submicron WC particles.